ANALISIS PENGARUH DIMENSI FRAUD DIAMOND TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA (Studi Kasus pada Mahasiswa S1 Jurusan Akuntansi Perguruan Tinggi Negeri Kota Malang) - I Dewa Made Satya Prawira; Gugus Irianto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aimed at examining the factors that influence students’ academic fraud behavior by using fraud diamond dimensions which consisted of pressure, opportunity, rationalization, and capability. This study used a mixed method with concurrent triangulation model to combine the quantitative and qualitative methods together, both during the data collection and data analysis. The samples of this study were 120 students and 5 informants from the undergraduate (S1) students majoring in accounting since 2011 who were active in the even semester in the academic year of 2014/2015 at the University of Brawijaya, the State University of Malang, and the State Islamic University of Maulana Malik Ibrahim Malang. This study found an evidence that the students’ academic fraud behavior was determined by fraud diamond dimensions. This study also explained why and how the students performed the academic fraud behavior, so that it could be an input to the relevant institutions to minimize the academic fraud behavior done by the students. Keyword : academic fraud behavior, pressure, opportunity, rationalization, and capability.